TRAINING AND MENTORING ON PACKAGING OPTIMIZATION OF POLINEMA CRISPY DUWET BANANA GEDEBOG CHIPS IN THE COMMUNITY OF DUWET VILLAGE, TUMPANG SUB-DISTRICT, MALANG DISTRICT - Lestari, Baroroh; Widiyowati, Eny; Suyono, Achmad; Anjari, Becik Gati; Poernamawati, Diana Eka; Pratama, Cahyo Ramadhan (Transpublika Publisher, 2023)
This PKM/Service program aims to improve the packaging and promotion of